Physical fighting among school-attending adolescents in El Salvador: an examination of the 2013 global school-based health survey - Omer, Mazin; Shaikh, Masood; Stiller, Mariella; Wilson, Michael (International journal of environmental research and public health, 2020)
Background: Violence among school-attending adolescents is an important public health problem worldwide. The present study examined demographic correlates for physical fighting behavior among a nationally representative sample of school-attending adolescents in El Salvador. Methods: Initial cross-tabulations to screen for correlations was then followed by logistic regression to understand the direction and the strength of selected demographic variables for physical fighting behavior, which occurred within a 12 month period of recall. Results: Out of a sample of 1910 school-attending adolescents in El Salvador, 11.5% reported having been involved in two or more physical fights during the recall period. Regression analyses indicated that being male (OR = 3.55; 95% CI = 2.11-6.00); having experienced bullying (OR = 2.16; 95% CI = 1.44-3.24); physical activity (OR 0.61; 95% CI 0.46-0.80); a sedentary lifestyle (OR 1.54; 95% CI 1.05-2.27), suicide planning (OR 2.28; 95% CI 1.46-3.56), and having non-understanding parents (OR = 1.45; 95% CI 1.06-1.98) were significantly associated with physical fighting among the sampled adolescents. Conclusion: Within the limitations of cross-sectional surveys conducted in school settings, the results of the present study suggest that giving attention to preventing bullying behavior among males and involving parents should be components of a multi-pronged strategy to preventing physical fighting in schools in El Salvador.